Design prototype of a smart household touch sensitive locker security system based on GSM technology - Zeyad, Mohammad; Ghosh, Susmita; Ahmed, S.M. Masum (Institute of Advanced Engineering and Science, 2019)
This paper illustrates a portable domestic locker security system which is based on GSM (Global System for Mobile Communications) technology. A handcrafted low-cost touch sensitive box is designed (using Vero board) for the project which is one of the most attractive features of the system. The system will operate in a way that if there is any unexpected user, tries to touch any portion of the touch sensitive box, a feedback system will be turned on immediately. The feedback system will alert the property holder about the unexpected user by sending SMS (Short Message Service) and turning on an alarm system. The alarm system will be turned off only if it receives a specific SMS from the property holder. This system not only has the advantages of high sensitivity, small size and lightweight, but also it is easy to use. This system is featured with an uncomplicated design, convenient use, strong flexibility and reliable performance. Since the circuit in the system is simple and easy to contrivance, the system can be installed without any difficulty at homes & offices. It will also provide a good security in the vehicles and Automated Teller Machine (ATM) booths.